2013
DOI: 10.1080/17458080.2012.750763
|View full text |Cite
|
Sign up to set email alerts
|

Influence of architecture on the Raman spectra of acid-treated carbon nanostructures

Abstract: Raman spectroscopy was used to characterise 11 varieties of carbon nanostructures (CNSs) consisting on seven varieties of commercial multi-walled carbon nanotubes, two types of carbon nanofibres and two types of lab-synthesised single-walled carbon nanotubes. The Raman spectra of these CNSs provided information on the structural ordering of the as-received (or as-synthesised) material. Additionally, the CNSs were chemically treated by two mixtures of nitric and sulphuric acids at markedly different concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…28,29 A narrow G-band is an indication of higher structural ordering and crystallinity. 29 Therefore, the intensity ratio of the D- and G-bands and the shape of these bands can be used to determine the structural ordering in the CNFs. It is clearly seen from Table 2 that increasing the GNP concentration decreased the I D / I G ratio of the pyrolyzed samples, indicating greater graphitization in the samples.…”
Section: Results and Discussionmentioning
confidence: 99%
“…28,29 A narrow G-band is an indication of higher structural ordering and crystallinity. 29 Therefore, the intensity ratio of the D- and G-bands and the shape of these bands can be used to determine the structural ordering in the CNFs. It is clearly seen from Table 2 that increasing the GNP concentration decreased the I D / I G ratio of the pyrolyzed samples, indicating greater graphitization in the samples.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This observation suggests that the structure of the SWCNTs underwent a consistent change during the electroplating process, possibly due to the presence of acetic acid in the plating bath. Prior research has suggested that nanotubes with low diameters and initial IG:ID > 1 are significantly susceptible to structural modification during acid treatment [47]. It was observed previously [42] that when Cu coating is less than 0.165 µm the oxide is CuO (with a Cu 2 O interface to Cu); however, when the coating is thicker than 0.165 µm the oxide is Cu 2 O.…”
Section: Compositionmentioning
confidence: 98%
“…This observation suggests that the structure of the SWCNTs underwent a consistent change during the electroplating process, possibly due to the presence of acetic acid in the plating bath. Prior research has suggested that nanotubes with low diameters and initial IG:ID > 1 are significantly susceptible to structural modification during acid treatment [47].…”
Section: Compositionmentioning
confidence: 99%
“… 46 The I D / I G ratio for G/CNT@NCNF decreased from 1.4 to 1.07 after acid treatment due to removal of amorphous and defective carbon from the CNF surfaces, thus, increasing the relative graphitic content. 47 In contrast, acid treatment increased the I D / I G ratio from 1.11 to 1.21 for GS@NCNF, which may be due to the removal of FeNi embedded graphene sheets from the CNF surfaces (Fig. S2 † ).…”
Section: Resultsmentioning
confidence: 96%